The Effect of Intercropping System of Corn (Zea mays, L.) and Peanut (Arachis hypogaea, L.) on Yield Production in Ungaran - Wibisana, Dharend Lingga; Budiyanto, Gunawan; Widyastuti, Titiek (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2017)
The research was conducted to examine transfer nitrogen from peanut to corn and determine the best planting time of peanut and corn which were cultivated by intercropping system. The research was conducted at dryland of Ungaran Central Java from December 2015 to April 2016. This research was complated using an experimental design with single factor, arranged in completely randomized block design. The treatments were monoculture system of corn (J), monoculture system of peanut (K), intercropping system: corn was planted two weeks after peanutÂ  (TS 1), intercropping system: peanut was planted two weeks after corn (TS 2), and intercropping system: corn and peanut were planted in the same timeÂ  (TS 3). Each treatment was replicated 3 times. The results showed that the transfer of nitrogen from peanuts to corn occured when the corn plants were in the stage of maximum vegetative growth. In this research, treatment TS 2 is the best planting time than other treatments as indicated by the yield of 4.02 tonnes corn per hectare.